Oxygen in the neonatal ICU: a complicated history and where are we now? - Rachna R. Mamidi; Cindy T. McEvoy (Frontiers Media S.A., 2024)
Despite major advances in neonatal care, oxygen remains the most commonly used medication in the neonatal intensive care unit (NICU). Supplemental oxygen can be life-saving for term and preterm neonates in the resuscitation period and beyond, however use of oxygen in the neonatal period must be judicious as there can be toxic effects. Newborns experience substantial hemodynamic changes at birth, rapid energy consumption, and decreased antioxidant capacity, which requires a delicate balance of sufficient oxygen while mitigating reactive oxygen species causing oxidative stress. In this review, we will discuss the physiology of neonates in relation to hypoxia and hyperoxic injury, the history of supplemental oxygen in the delivery room and beyond, supporting clinical research guiding trends for oxygen therapy in neonatal care, current practices, and future directions.